2015
DOI: 10.1021/acs.biochem.5b00842
|View full text |Cite
|
Sign up to set email alerts
|

Pif97, a von Willebrand and Peritrophin Biomineralization Protein, Organizes Mineral Nanoparticles and Creates Intracrystalline Nanochambers

Abstract: The formation of the mollusk nacre layer involves the assembly and organization of mineral nanoparticles into fracture-toughened mesoscale-sized aragonite tablets that possess intracrystalline nanoporosities. At least one nacre protein family, known as the framework proteome, is strategically located as part of a macromolecular coating around each nacre tablet and is believed to participate in tablet formation. Here, we report new studies of a recombinant form (rPif97) of a unique Japanese pearl oyster (Pincta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
220
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(238 citation statements)
references
References 46 publications
18
220
0
Order By: Relevance
“…These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion. What was discovered was very informative: these proteins are distinguishable in terms of what mineral species or steps in the non-classical scheme they affect (Figure 4) [58][59][60][61][62][63][64][65][66][67]. Further, using mineralization assays which overlap with the time periods of the potentiometric titrations and utilize similar solution and supersaturation conditions [58][59][60][61][62][63][64][65][66][67] these studies demonstrated that these proteins form hydrogels that can capture, assemble, and organize mineral nanoparticles ( Figure 5) [62,65] consistent with CPA theory [15].…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion. What was discovered was very informative: these proteins are distinguishable in terms of what mineral species or steps in the non-classical scheme they affect (Figure 4) [58][59][60][61][62][63][64][65][66][67]. Further, using mineralization assays which overlap with the time periods of the potentiometric titrations and utilize similar solution and supersaturation conditions [58][59][60][61][62][63][64][65][66][67] these studies demonstrated that these proteins form hydrogels that can capture, assemble, and organize mineral nanoparticles ( Figure 5) [62,65] consistent with CPA theory [15].…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 98%
“…As an example, recent in vitro studies involving five recombinant mollusk shell nacre-associated proteins [58][59][60][61][62][63][64][65][66] and ACC-stabilizing sea urchin spicule matrix proteins [67,68] have utilized mineralization assay conditions identical to those employed in non-classical nucleation studies [29][30][31][32][33]. What links these different biomineralization proteins together are two common molecular themes [69,70]: intrinsic disorder, or absence of folding protein structure, and amyloid-like aggregation-prone domains, which promote protein-protein association leading to the formation of protein phases or hydrogels [58][59][60][61][62][63][64][65][66][67][68]. These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion.…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This feature gives the nanoparticles additional surface area reflecting the porosity of the individual aggregates and this in turn may lead to changes in environmental adsorption, optical properties and pseudocapacitor performance. [9][10][11][12][13][14][15][16] Nanoporosities can be probed, traditionally, via ex situ gas adsorption isotherm measurements such as the BrunauerEmmett-Teller (BET) method; molecules, such as nitrogen or argon, are used. Such measurements are invaluable for the application of porous nanoparticles for gas-solid studies, for example in catalysis or sensing, and a careful analysis of the measured absorption isotherm may give insight into the shape and size of the particle pores as well as information about the total surface area covered by the adsorbate probe.…”
Section: Introductionmentioning
confidence: 99%